A new looming of Middle East respiratory syndrome coronavirus MERS-CoV (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Middle East Respiratory Syndrome Coronavirus is the species of genus Beta Coronavirus. A novel human coronaviruses are single-stranded RNA. They are distinct from SARS and common cold viruses. First case of MERS-CoV was reported in Saudi Arabia in April 2012, in patients with severe Pneumonia. MERS-CoV has mild to non-specific symptoms which includes Headache, vomiting, High fever, cough, etc. MERS-CoV has been reported under high mortality rate. It is diagnosed through PCR (Polymerase Chain Reaction) and virus isolation from respiratory tracts and blood samples. No Antiviral agents or vaccines are available for this disease.